Characterization of unsaturated coarse-grained railway embankment fill: Water retention and dilatancy - Yuanjie Xiao; Wenqi Li; Liuxin Chen; Xiaoming Wang; Yunbo Li; Pan Tan; Jiapei Du (Journal of Rock Mechanics and Geotechnical Engineering)
This study investigated the hydraulic and mechanical behaviors of unsaturated coarse-grained railway embankment fill materials (CREFMs) using a novel unsaturated large-scale triaxial apparatus equipped with the axis translation technique (ATT). Comprehensive soil-water retention and constant-suction triaxial compression tests were conducted to evaluate the effects of initial void ratio, matric suction, and confining pressure on the properties of CREFMs. Key findings reveal a primary suction range of 0–100 kPa characterized by hysteresis, which intensifies with decreasing density. Notably, the air entry value and residual suction are influenced by void ratio, with higher void ratios leading to decreased air entry values and residual suctions, underscoring the critical role of void ratio in hydraulic behavior. Additionally, the critical state line (CSL) in the bi-logarithmic space of void ratio and mean effective stress shifts towards higher void ratios with increasing matric suction, significantly affecting dilatancy and critical states. Furthermore, the study demonstrated that the mobilized friction angle and modulus properties depend on confining pressure and matric suction. A novel modified dilatancy equation was proposed, which enhances the predictability of CREFMs' responses under variable loading, particularly at high stress ratios defined by the deviatoric stress over the mean effective stress. This research advances the understanding of CREFMs' performance, especially under fluctuating environmental conditions that alter suction levels.